2012
DOI: 10.1007/s11010-011-1219-1
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV prevents MPP+-induced SH-SY5Y cell death via the inhibition of Bax-mediated pathways and ROS production

Abstract: Parkinson's disease (PD) is characterized by a progressive degeneration of dopaminergic neurons in the substantia nigra. Oxidative stress and neural degeneration are suggested to be involved in the pathogenesis of PD. Previous studies have revealed that Astragaloside IV (AS-IV) can reduce inflammation and oxidation, making it a potential therapeutic agent for neurodegenerative disease. In this study, we investigated whether AS-IV protect against 1-methyl-4-phenylpyridnium ion (MPP(+))-induced dopaminergic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 47 publications
3
53
0
Order By: Relevance
“…A recent study reported that in SH-SY5Y cells, AS-IV significantly reversed MPP+-induced elevated activity of caspase-3 (35). We carried out western blot to investigate the effects of AS-IV on caspase-3 in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that in SH-SY5Y cells, AS-IV significantly reversed MPP+-induced elevated activity of caspase-3 (35). We carried out western blot to investigate the effects of AS-IV on caspase-3 in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, AS-IV was demonstrated to exert notable protective effects against MPP + -induced oxidative damage in SH-SY5Y neuroblastoma cells (41). However, the antioxidant mechanism of AS-IV remains unclear.…”
Section: Discussionmentioning
confidence: 96%
“…Rg1 activates the Wnt/β-catenin signaling pathway in vivo and in vitro, thus exerting a protective effect against neurodegeneration (38). AS-IV has been used as an effective treatment for ischemia-reperfusion injury, myocardial infarction and type 2 diabetes (21,39,41). The protective functions of AS-IV are attributed to an increased cellular content and activity of superoxide dismutase (SOD), and the inhibition of calcium pumps.…”
Section: Discussionmentioning
confidence: 99%
“…Human neuroblastoma SH-SY5Y cells (NCCS, Pune), possess morphological, biochemical, and electrophysiological characteristics of dopaminergic neurones and have been widely used in the study of cell model for PD [7]. Cells were cultured in DMEM+F12 supplemented with 10% (v/v) heat-inactivated foetal calf serum and 100 units/ml penicillin/streptomycin.…”
Section: Cell Culture Maintenance and Treatmentmentioning
confidence: 99%